Climate Risk Management in Agricultural Extension Curriculum Validation and Training of Trainers Workshop in Kenya - Grossi, Amanda; Dinku, Tufa; Hansen, James; Trzaska, Sylwia; Ruirie, Onesmus; Crane, Todd A. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Climate change and year-to-year climate variability have resulted in widespread, pervasive impacts to ecosystems and people in Africa, including increases in the intensity of weather extremes such as droughts and floods. While these shifting and varying temperature and precipitation patterns have affected the productivity of many climate-sensitive sectors, the agricultural sector has been the most impacted, resulting in reduced food availability and increased food prices, ultimately jeopardising food security, nutrition, and livelihoods of millions of people. Despite the enormous role that climate information can and has played in supporting resilience of agricultural and food systems and the availability of high-quality climate information in many Africa countries, including through the Enhancing National Climate Services (ENACTS) initiative, however, the effective use of climate information in decision-making processes to support climate adaptation has remained limited. This reality persists despite strong policy and enabling environments in many of these countries and despite significant investments in climate information and services through national and sectoral strategies, policies, and programs.